(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
Settlements in Valleys are the main type of human settlements in mountainous terrain. In the study of Guizhou, the typical mountainous province in southwestern China, we take valley as a important space unit for studying the formation and evolution of a single settlement and of group of settlements. Taking four typical valley areas within minority group regions as examples, the paper analyzes the existence, the reproduction, the migration of foreign community presence and the interaction among settlements in these valley, and discusses the distribution of rules of settlement groups in the valley for the selected case studies. Â